Diatoms from small ponds and terrestrial habitats in Deserta Grande Island (Madeira Archipelago) - Gonçalves, Vítor (2021)
Freshwater diversity, and diatoms in particular, from Desertas Islands (Madeira Archipelago, Portugal) is poorly known, although the Islands are protected and became a Natural Reserve in 1995. During two field expeditions in 2013 and 2014 to Deserta Grande Island, several freshwater and terrestrial habitats were sampled. The analysis of these samples aims to contribute to the biodiversity assessment of the freshwater biota present in Deserta Grande Island. Here, we present the diatom diversity in Deserta Grande Island resulting from that survey. This study contributes to improve the knowledge of Madeira Archipelago freshwater diversity, particularly in the Desertas sub-archipelago.New information To our knowledge, we present the first diatom data for the Desertas sub-archipelago. This work resulted in a list of 60 diatom taxa for Deserta Grande, from which 57 were identified to species level. From the 60 new records for Desertas sub-archipelago, 30 of them were also new records for Madeira Archipelago. Several specimens could not be assigned to a known species and may be new diatom species not yet described.